2020
DOI: 10.1002/1878-0261.12814
|View full text |Cite
|
Sign up to set email alerts
|

TRAP1 enhances Warburg metabolism through modulation of PFK1 expression/activity and favors resistance to EGFR inhibitors in human colorectal carcinomas

Abstract: Here, we show that TRAP1 modulates glycolytic metabolism by regulating PFK1 activity/stability. In a high TRAP1 background, TRAP1 inhibits cellular respiration and interacts with PFK1 on the ER and this enables PFK1 glycolytic activity preventing its ubiquitination/degradation. In a low TRAP1 background, cellular respiration is upregulated and PFK1 activity reduced due to increased ubiquitination/degradation and this results in loss of TRAP1 control on glycolytic cascade. The increased levels of citrate, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…Our data suggested that C501 oxidation is a mediator of AF toxicity, and we found that C501S mutation decreased the cell sensitivity to AF treatment. As previously reported, TRAP1 C501 S -nitrosylation impacts its protein expression levels and ATPase activity, both important for TRAP1 role in regulating the Warburg effect and sensitivity to drugs [ 63 , 64 , 98 , 99 ]. Here, the observed decreased sensitivity of the TRAP1 C501S mutant to AF agrees with the effects of C501 S -nitrosylation shown in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Our data suggested that C501 oxidation is a mediator of AF toxicity, and we found that C501S mutation decreased the cell sensitivity to AF treatment. As previously reported, TRAP1 C501 S -nitrosylation impacts its protein expression levels and ATPase activity, both important for TRAP1 role in regulating the Warburg effect and sensitivity to drugs [ 63 , 64 , 98 , 99 ]. Here, the observed decreased sensitivity of the TRAP1 C501S mutant to AF agrees with the effects of C501 S -nitrosylation shown in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…The effects of TRAP1 on mitochondrial respiration are still controversial: TRAP1 silencing increases oxygen consumption in SAOS-2 osteosarcoma cells, PEA1 ovarian cancer cells, HCT116 colorectal carcinoma cells and mouse fibroblasts [ 7 , 8 , 17 , 18 ]; however, TRAP1 silencing or treatment with the mitochondria-directed HSP90 inhibitor Gamitrinibs reduces oxygen consumption and ATP production in PC3 prostate cancer cells and in LN229 glioblastoma cells, although in the specific metabolic context of low glucose availability [ 9 ]. To shed light on this complex scenario, as a preliminary approach we first analyzed the response of TRAP1 knock-down cells to a decreased glucose availability through the monitoring of AMPK activation over time and identified a significant AMPK phosphorylation after 4 h of glucose withdrawal (referred to as "low glucoseā€ hereafter), specifically in TRAP1-expressing cells (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, male sterility due to malfunction of the MMI system is indeed a loss for species preservation, and it seems that some kind of defense system coexists. Fmr1 is involved in spermatogenesis, axoneme synthesis, and the Warburg effect (Zhang et al, 2004;Maddalena et al, 2020), and its function is very similar to that of SPAG1, so it may control SPAG1-2 expression as an RNA-binding translational regulatory protein. If the SPAG1-2 / Eri15 axis runs out of control due to widespread loss of Fx-mir, it may be that the misexpressed FMRP suppresses the translation of SPAG1-2 mRNA.…”
Section: Xt-mir and Spag1mentioning
confidence: 99%